The Spiritual Exercises of John Rawls. (June 2022) - Lefebvre, Alexandre
In this article I interpret John Rawls's concept of the original position as a spiritual exercise. In addition to the standard interpretation of the original position as an expository device to select principles of justice for the fundamental institutions of society, I argue that Rawls also envisages it as a "spiritual exercise": a voluntary personal practice intended to bring about a transformation of the self. To make this argument, I draw on the work of Pierre Hadot, a philosopher and classicist, who introduced the idea of spiritual exercises as central to ancient and modern conceptions of philosophy. By reading Rawls alongside Hadot, this article portrays Rawls as a thinker deeply concerned with the question of how subjects can lead more just and fulfilling lives. It also proposes that the original position as a spiritual exercise can help defend liberalism as a social and political doctrine.